The Impact of Gross Domestic Product on Co2 Emissions (A Case Study of Asian Tiger Countries) (London Journal of Research In Management & Business, 2025)
This research examines the impact of Gross Domestic Product (GDP) on CO2 emissions in four well-developed Asian countriesSouth Korea, Singapore, Taiwan, and Hong Kongover the period from 1960 to 2019. To analyze the relationships, regression was performed using the Generalized Least Squares (GLS) method in STATA-14. The results indicate that all regressors are significant, and to address the issue of autocorrelation in the model, an Autoregressive Lag model was used. By adding the lag of an independent variable to the model, the problem of autocorrelation was resolved. Consequently, the model's goodness-of-fit improved, and the significance levels of the regressors were confirmed. Based on the research findings, it can be concluded that the economic growth of these countries leads to an increase in carbon dioxide emissions into the external environment.
Keywords: Nigeria; Cybersecurity threats; demand/supply side of financial inclusion; and OLS/2SLS/GMM; digitalization; manager; value-based orientations; formation of value-based orientations; business; Correlation; Gross Domestic Product; CO2 emissions; GLS method; STATA14; Autoregressive Lag model; coefficient of determination.